Utilization Pattern of Health Care Services at Village Level - Yadav, D K (Journal of Nepal Health Research Council, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Primary health care service is basic essential health care. Due to lack of access to quality health care services, many rural people suffer from various health related problems. The objective of this study was to assess how health care services are utilized by beneficiaries in two different villages in Dhanusha district of Nepal. Methods: A descriptive cross sectional study was conducted in two Village Development Committees with sixty four households selected randomly from January 1, to February 27, 2008. Results: The study shows that 48 and 21 percent of population were utilizing local available health services respectively within and beyond 2 km from the health facility. It revealed that distance was significant indicator for utilization of health services. Study also shows that those in VDC1 had availed maximum (67%) service of trained man power for delivery as compared to those in VDC 2, (20%) where most (80%) of deliveries were conducted by relatives and neighbours, the difference was significant. Conclusions: Distance from the heath services is an important factor for utilization of health resources. The utilization of health facility was satisfactory but the quality of services was not satisfactory. Key words: accessibility, availability, health care services,health resources,manpower